2021
DOI: 10.1038/s41598-021-03752-4
|View full text |Cite
|
Sign up to set email alerts
|

Extractable quantum work from a two-mode Gaussian state in a noisy channel

Abstract: We study a Szilard engine based on a Gaussian state of a system consisting of two bosonic modes placed in a noisy channel. As the initial state of the system is taken an entangled squeezed thermal state, and the quantum work is extracted by performing a measurement on one of the two modes. We use the Markovian Kossakowski-Lindblad master equation for describing the time evolution of the open system and the quantum work definition based on the second order Rényi entropy to simulate the engine. We also study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Using quantum teleportation protocols an unknown quantum state can be teleported, in other words, reproduced at the receiver part using the receivers resource state mode and the results of measurements performed by the sender over the initials state and communicated to the receiver via classical channel. 2 During the quantum teleportation process the initial state is destroyed, which puts it into agreement with the no-cloning theorem.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Using quantum teleportation protocols an unknown quantum state can be teleported, in other words, reproduced at the receiver part using the receivers resource state mode and the results of measurements performed by the sender over the initials state and communicated to the receiver via classical channel. 2 During the quantum teleportation process the initial state is destroyed, which puts it into agreement with the no-cloning theorem.…”
Section: Introductionmentioning
confidence: 74%
“…However with the increase of the distance, time of teleportation also increases, which leads to decoherence in the system. 2 Quantum teleportation of a pure Gaussian state was studied in the work . It was shown that the increase of fidelity of teleportation with the squeezing between the resource state modes and of the entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of quantum teleportation, the shared entangled state between the sender and receiver serves as a critical resource. Recent research has emphasized that to achieve SQT a Ądelity of teleportation higher than 2/3 is required and the resource state must ex-hibit two-way steerability, a quantum correlation phenomenon that surpasses the strength of mere entanglement [13,41,42,43,44,45,46,47,48]. These essential conditions for twomode Gaussian states are summarized in the following subsections, namely, Subsections 2.1 and 2.2.…”
Section: Secure Quantum Teleportationmentioning
confidence: 99%
“…Thus, carrying out these concepts into the quantum realm is not a straightforward task. However, developments in stochastic thermodynamics 49 , 50 , open quantum systems 11 , 51 , and quantum information theory 52 , 53 have led to significant progress in these efforts.…”
Section: Thermodynamic Settingmentioning
confidence: 99%